2001
DOI: 10.1038/sj.leu.2402142
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of cytogenetics is reinforced by the kind of induction/consolidation therapy in influencing the outcome of acute myeloid leukemia – analysis of 848 patients

Abstract: We studied the impact of cytogenetics and kind of induction/consolidation therapy on 848 adult acute myeloid leukemia (AML) patients (age 15-83). The patients received three types of induction/consolidation regimen: standard (daunorubicin and cytosine arabinoside (3/7); two cycles); intensive (idarubicin, cytosine arabinoside and etoposide (ICE), plus mitoxantrone and intermediate-dose Ara-C (NOVIA)); and low-dose (low-dose cytosine arabinoside). CR patients under 60 years of age, if an HLA-identical donor was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 25 publications
5
42
0
Order By: Relevance
“…[2][3][4][5] Other currently recognized risk factors associated with a worse outcome include older age and development of acute or chronic GVHD. [6][7][8] The aim of this single-center retrospective study was to review the clinical characteristics and evaluate the potential predictors of RFS and OS in unrelated vs sibling donor HCT. Therefore, we analyzed the data of 92 consecutive adult patients with AML and myelodysplastic syndrome (MDS) undergoing their first peripheral blood-derived HCT from related or unrelated donors at the University of Freiburg Medical Center between 1996 and 2006 after treatment with a uniform preparative regimen consisting of high-dose oral BU and CY.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Other currently recognized risk factors associated with a worse outcome include older age and development of acute or chronic GVHD. [6][7][8] The aim of this single-center retrospective study was to review the clinical characteristics and evaluate the potential predictors of RFS and OS in unrelated vs sibling donor HCT. Therefore, we analyzed the data of 92 consecutive adult patients with AML and myelodysplastic syndrome (MDS) undergoing their first peripheral blood-derived HCT from related or unrelated donors at the University of Freiburg Medical Center between 1996 and 2006 after treatment with a uniform preparative regimen consisting of high-dose oral BU and CY.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we were interested in the better molecular understanding of a clinical homogenous subgroup with a poor prognosis (AML with monosomy 7 or deletion 7q (À7/del7q)). [5][6][7][8] We analyzed samples from AML patients with À7/del7q, AML patients with normal karyotype (without FLT3 mutation) and normal bone marrow stem cells of healthy individuals, by gene expression profiling. Comparison of these three groups showed that the expression of SKI, a nuclear co-repressor of the HDAC complex, is highly upregulated in À7/del7q AML.…”
Section: Introductionmentioning
confidence: 99%
“…8 For patients transplanted in CR1, cytogenetic pattern is also a significant predictor of outcome. [4][5][6][7][9][10][11][12] We were interested in evaluating these factors, as well as determining whether quantification of residual disease at the time of transplant was correlated with outcome. We were particularly interested in evaluating whether the percentage of residual bone marrow blasts, and/or detection of residual disease by cytogenetic analysis, affected the outcome after SCT.…”
mentioning
confidence: 99%